I am done with this! Women dropping out of engineering majors - González-Pérez, Susana; Martínez-Martínez, Miryam; Rey-Paredes, Virginia; Cifre, Eva (Frontiers in Psychology, 2022)
Women are still underrepresented in STEM careers (Science, Technology, Engineering and Mathematics). One of the possible drivers behind this gender gap in the labour market is the female dropout from STEM education. The causes of the gender differences in the persistence of pursuing STEM studies have been explained by multiple factors related to interest and resolution in this type of career. The goal of the present research is to study the STEM persistence gender gap in higher education by exploring the main factors underlying the leakage in the pipeline of STEM fields. Our study reports the results of 34 qualitative in-depth interviews where internal barriers, stereotypes and external obstacles are assessed by women who have left their university degrees, compared with men who have withdrawn and women who have persisted. Results from the content analysis suggest that the undermining of persistence in STEM fields is related to factors such as the chilly and hostile environment in classes or the workload from an excessively demanding curriculum. Other factors affecting women’s withdrawal are the lack of role models and the perceived incongruity between the female gender role and STEM roles in society, leading to a weakening of female students’ self-efficacy and eroding their sense of belongingness, even making them consider dropping out of their STEM career. These findings provide information for the design of future STEM interventions aimed to enhance women’s persistence in STEM university studies.